Effects of Ultrasound-Assisted Extraction and Solvent on the Phenolic Profile, Bacterial Growth, and Anti-Inflammatory/Antioxidant Activities of Mediterranean Olive and Fig Leaves Extracts - Cristina Alcántara; Tihana Žugčić; Radhia Abdelkebir; Jose V. García-Pérez; Anet Režek Jambrak; José M. Lorenzo; María Carmen Collado; Daniel Granato; Francisco J. Barba (Molecules, 2020)
Mediterranean plants, such as fig and olive leaves, are well-known to exert beneficial effects in humans because of the presence of a wide range of bioactive compounds. However, scarce information regarding the impact of extraction methods, such as ultrasound and types of solvents, on their profile of antioxidant and anti-inflammatory compounds is provided. In addition, no information is available on the effects of extraction methods and solvents on the inhibition of pathogenic bacteria or promoting probiotic growth. In this scenario, this study was aimed to study the effects of ultrasound-assisted extraction (UAE) and solvent on the phenolic profile (Triple TOF-LC-MS/MS), antioxidant and anti-inflammatory compounds of olive and fig leaves. Results showed that UAE extracted more carotenoids compared to conventional extraction, while the conventional extraction impacted on higher flavonoids (olive leaves) and total phenolics (fig leaves). The antioxidant capacity of aqueous extract of fig leaves was three times higher than the extract obtained with ethanol for conventional extraction and four times higher for UAE. In general terms, hydroethanolic extracts presented the highest bacterial growth inhibition, and showed the highest anti-inflammatory activity. In conclusion, these side streams can be used as sources of bioactive compounds for further development of high-added-value products.